A qualitative social representations study of conspiracy theories in Greece - Dimakis, Antonis; Griva Artemis Μ.; Hantzi, Alexandra; Chryssochoou, Xenia (Psychology: the Journal of the Hellenic Psychological Society, 2025)
This qualitative study aims to examine conspiracy theories (CTs) circulating on the internet in Greece during times of crisis (2010-2020). Informed by a social representations approach, we examined the organization of the CTs content, the construction of intergroup conflicts and dichotomies involved, and the factors that organize the representational field. A lexicometrical analysis using the IraMuTeQ software was conducted on a corpus of 140 texts found online. A Descending Hierarchical Analysis revealed four classes of CTs, named a) Conspiracies of ruling national elites against the Greek nation b) New World Order against People, c) Science Vs People: denying climate change as human activity outcome, and d) Attacking the “essence” of individuals: their body and identity. The former two classesdescribed intergroup conflicts relating to economic, political, and global power, whereby people are opposed to national and supranational elites. The latter two classes tapped conspiracies against human beings in terms of biopolitics or climate change, whereby people are opposed to scientists. Finally, a Correspondence Analysis revealed two factors structuring the representational field: a) A principle separating conspiracies referring to intergroup conflict Vs conspiracies referring to biopolitics and climate change and b) a principle separating two types of intergroup conflict: within the nation and globally. Results are discussed in relation to SRT and the way CTs contribute to social meaning-making in times of crisis.